Grain boundary engineering of new additive manufactured polycrystalline alloys - Frank Abdi (Elsevier, 2021)
A novel idea to create new alloys for Additive manufacturing (AM) by mixing a small addition of nanoparticles with bulk material was put forward. Integrated Computational Material Engineering (ICME) may be used to guide the AM process, predict thermal behaviour, optimize process parameters, secure net-shape, and qualify parts. Modelling is needed to predict the effect of defects and the effect of inclusions on mechanical properties, build quality and in-service performance. ICME can reduce trial-and-error fabrication and establish an AM digital twin, thereby accelerating part qualification and AM adoption. AM creates complex thermal processes which impact material microstructure and result in changes to mechanical properties in terms of strength and plasticity. In this study, Grain-Boundary Engineering (GBE) and multi-scale modelling are performed to expedite qualification of new and existing AM polycrystalline alloys.AM parts exhibit cracks, low toughness, low plasticity, and high residual stresses. To mitigate these characteristics, a methodology for GBE and microstructural control was developed. Depending on part requirements a low angle, coincident site lattice, or high angle grain boundary (LAGB,CSL, HAGB) might be the preferred option. For example, HAGB occurs in equiaxed grain microstructure, prevents precipitation and crystallization formation, and inhibits cracks and corrosion. Some polycrystalline materials may be non-weldable and exhibit cracks. Microstructural control can be used to address this phenomenon. AM offers unique advantages over casting, including material composition change and unique thermal processing. By utilizing nano-inclusions, cracks may be mitigated and AM parts improved.ICME physics-based approach is used to implement GBE modelling to improve the microstructure of an AM polycrystalline material from Equiaxed/HAGB to LAGB and CSL considering nano-scale inclusions. The ICME tool integrates meltpool engineering; thermal transport; nano-micro-mechanics; material characterization; calibration and qualification; Voronoi-tessellation, finite element modelling, and design of experiment optimization. With this background, ICME predicts time-temperature transformation, thermal properties, process map, meltpool size, precipitation, porosity, and effects of nano inclusions. In this manner, ICME helps determine ideal AM machine parameters that secure qualified parts as a consequence of the AM process.In this study, mechanical properties and fracture toughness were validated against test. Predictions included creep, crack growth, and the effect of precipitates and voids under in-service crack growth behaviour. Stainless steel (SS316L) dog bones specimens were printed and stress relieved by air and water cooling supported by fractography and imaging. The objective of this effort was to develop technologies and processes in AM design and engineering that could predetermine the microstructure of AM parts. Future efforts will employ the tool to tailor grain boundaries to produce predictable mechanical properties - including mode of failure.